A Critical Linguistic analysis of the representation of Muslims in The New York Times - Lemmouh, Zakaria (HERMES - Journal of Language and Communication in Business, 2008)
The aim of this study is to shed light on recurring lexical and syntactic features that contribute to a stereotyped image of out-groups in newspapers. The focus of the study is on articles relating to Muslims in The New York Times. The analysis is based on the analytic paradigm of Critical Linguistics (CL) and Corpus Semantics (CS). The results show that the linguistic features analysed point to a systematic ‘othering’ and stereotyping of Muslims as compared to other participants. The study concludes with a discussion on how the grammatical features examined work together to project a stereotyped image of Muslims and how the analytical method of Critical Linguistics (CL) copes with a quantitative analysis of a great deal of randomly chosen data from a corpus consisting of newspapers from the New York Times.